Synthesis of trifluoromethyl N, N-aminals from nitrogen containing heterocycles by using a plasma flow microreactor. Issue 28 (20th March 2023) - Abedelnour, Elias; Ognier, Stephanie; Venier, Olivier; Schio, Laurent; Tatoulian, Michael; Cossy, Janine
Abstract : Trifluoromethyl N, N -aminals were synthesized from nitrogen containing heterocycles in a R3 SiCF3 solution, using an argon plasma in a flow microreactor. The transformation of the trifluoromethyl N, N -aminals to N -trifluoroethylamine is also reported. Abstract : Trifluoromethyl N, N -aminals are important precursors allowing access to fluorinated building blocks. In this work, the direct synthesis of trifluoromethyl N, N -aminals from nitrogen containing heterocycles is reported using argon plasma in a continuous flow microreactor without any additives or metal catalysts. Their transformation to N -trifluoroethyl amines is also reported.